PENERAPAN MEDIA CANVA INTERAKTIF DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA SMK DARUL A’MAL LAMPUNG - Sawali Fahrizal Kurnia (STKIP Pesisir Selatan, 2026)
This study aims to deeply analyze the planning, implementation, and evaluation stages of using Canva based presentation design to increase student learning motivation in the Islamic Religious Education subject at SMK Darul Amal. This research employed a qualitative approach with a case study design. Data were collected through classroom observation, unstructured interviews with one teacher and twelve eleventh grade students, and document analysis. The collected data were validated using triangulation and analyzed using the Miles and Huberman interactive model. The results revealed that planning which integrated visual aesthetics successfully captured students' initial attention. During the implementation stage, students did not merely listen to lectures but actively engaged in groups to design Islamic history posters using laptops. This direct involvement was evaluated to have a major impact on increasing learning motivation, evidenced by the elimination of boredom, longer focus spans, and increased student confidence to participate in discussions. The novelty of this study lies in the shifting function of the Canva application, which was originally used strictly as a one-way presentation media by the teacher, transforming into a collaborative workspace that perfectly matches the practical learning characteristics of vocational high school students.